1995
DOI: 10.3171/jns.1995.82.4.0600
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation of human cerebral meningioma cells by suramin: effects on cell growth, cell cycle phases, extracellular growth factors, and PDGF-BB autocrine growth loop

Abstract: The growth of human cerebral meningiomas depends on various growth factors, including epidermal growth factor (EGF), transforming growth factor (TGF)-alpha and TGF-beta, platelet-derived growth factor (PDGF)-BB, insulin-like growth factor (IGF)-I and IGF-II, and acidic and basic fibroblast growth factors. The latter three have been shown to form autocrine loops that are thought to be a major component of uncontrolled growth in meningioma tissue. Suramin is known to prevent binding of a variety of growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 36 publications
3
24
0
3
Order By: Relevance
“…Consistently with involvement of ERK 1/2 in cisplatin toxicity, we found that PD98059, is a MEK inhibitor and suramin, a polysulphonated compound previously used as inhibitor of extracellular receptors for growth factors [Schrell et al, 1995;Li et al, 1999;Laubinger et al, 2003], not only inhibited ERK 1/2 activation but also reduced the extent of CDDP-induced cell death. These compounds, which can both block the upstream signaling to ERK 1/2, are also able to significantly reduce the Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Consistently with involvement of ERK 1/2 in cisplatin toxicity, we found that PD98059, is a MEK inhibitor and suramin, a polysulphonated compound previously used as inhibitor of extracellular receptors for growth factors [Schrell et al, 1995;Li et al, 1999;Laubinger et al, 2003], not only inhibited ERK 1/2 activation but also reduced the extent of CDDP-induced cell death. These compounds, which can both block the upstream signaling to ERK 1/2, are also able to significantly reduce the Fig.…”
Section: Discussionsupporting
confidence: 55%
“…23A2 myoblasts cultured in naive DM which has been boiled identically had no a ect on their abiity to express MHC or fuse (d.n.s.). The actions of many peptide growth factors are abrogated by the non-speci®c antagonist, suramin (Schrell et al, 1995). 23A2 myoblasts cultured in DM supplemented with suramin express MHC to the same level as cells cultured without suramin (Figure 4b).…”
Section: Mhcmentioning
confidence: 99%
“…Esses fatores de crescimento ligam-se a receptores celulares específicos, os receptores tirosina-quinase. Vários estudos demonstram a expressão de diversos fatores de crescimento como o fator de crescimento epidérmico (EGF), o fator de crescimento derivado das plaquetas (PDGF) e o VEGF pelas células tumorais de meningiomas in vitro e in vivo 3,24 . Esses fatores de crescimento têm provavelmente uma atividade de estimulação autócrina de proliferação das células neoplásicas.…”
Section: Incidência Deunclassified
“…Esses fatores de crescimento têm provavelmente uma atividade de estimulação autócrina de proliferação das células neoplásicas. A suramina, droga que se liga a uma série de fatores de crescimento como o EGF, o PDGF, o fator de crescimento de fibroblastos (FGF-b), entre outros, inibe a proliferação de células de meningiomas em cultura 24 . Os efeitos de estimulação parácrina dos fatores de crescimento expressos nas células dos meningiomas permanecem em investigação.…”
Section: Incidência Deunclassified